2008
DOI: 10.1093/jac/dkm523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of extended-spectrum  -lactamase-producing isolates of Haemophilus parainfluenzae

Abstract: The high-level cefotaxime resistance in the H. parainfluenzae isolates was due to a combination of a plasmid-mediated TEM-15 extended-spectrum beta-lactamase with altered PBP3 probably contributing. Other contributing resistance mechanisms could not be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…3,6 Although H. parainfluenzae is often resistant to b-lactam antibiotics, its mechanisms of resistance to this class of antibiotics have received little attention. The BLNAR mechanism has been very rarely reported in H. parainfluenzae, 7 and, to our knowledge, the production of inhibitor-resistant TEM (IRT) b-lactamases has not been described in clinical isolates of Haemophilus spp., although their effect has been studied in artificially produced recombinant strains. 8 Accordingly, the aims of this study were to determine the mechanisms of resistance to b-lactam antibiotics in clinical isolates of H. parainfluenzae and to elucidate the impact that b-lactam resistance genotypes have on the antibiotic susceptibility of H. parainfluenzae.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…3,6 Although H. parainfluenzae is often resistant to b-lactam antibiotics, its mechanisms of resistance to this class of antibiotics have received little attention. The BLNAR mechanism has been very rarely reported in H. parainfluenzae, 7 and, to our knowledge, the production of inhibitor-resistant TEM (IRT) b-lactamases has not been described in clinical isolates of Haemophilus spp., although their effect has been studied in artificially produced recombinant strains. 8 Accordingly, the aims of this study were to determine the mechanisms of resistance to b-lactam antibiotics in clinical isolates of H. parainfluenzae and to elucidate the impact that b-lactam resistance genotypes have on the antibiotic susceptibility of H. parainfluenzae.…”
Section: Introductionmentioning
confidence: 90%
“…Due to the high degree of nucleotide (78%) and amino acid (83%) homology between ftsI and PBP3 of H. influenzae Rd KW20 and H. parainfluenzae T3T1, 7,13 we used the same genotype classification as that already used for H. influenzae, 3,15 as follows: gBLNAS, b-lactamase-negative isolates that are ampicillin susceptible without resistance mechanisms; gBLNAR, b-lactamase-negative isolates with PBP3 amino acid substitutions causing reduced susceptibility to ampicillin (defined by either an Asn526 or an Arg517 substitution); gBLPAR, b-lactamase-positive isolates that are ampicillin resistant without gBLNAR-defining PBP3 amino acid substitutions; and gBLPACR, b-lactamase-positive isolates also presenting PBP3 amino acid substitutions.…”
Section: Genotype Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, little attention has been paid to Haemophilus parainfluenzae. Only a few BLNAR and/or TEM-producing isolates have been described (4,5), and those with resistance to quinolones are rarely reported (6,7). To our knowledge, MDR H. parainfluenzae isolates (e.g., simultaneously resistant to ␤-lactams, quinolones, and macrolides) have never been found.…”
mentioning
confidence: 95%
“…27 The β-lactamases detected include the TEM-1 and TEM-15 types, which are usually associated with plasmids. 14,16,28,29 It was reported that the plasmid that carried the TEM-1 β-lactamase was identical to one isolated from 'Africantype' penicillinase-producing Neisseria gonorrhoeae strain. 26,30 Inhibitor resistant β-lactamases TEM-34 and TEM-182, which were both carried by TnA transposon of the Tn2 type, were also detected in H. parainfluenzae in 2011.…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%